WHO SRQ-20 Outcomes in Mothers of Children 6-23 Months By Fecal Disposal and Drinking Water Source Factors - Saefurrohim, Muhamad Zakki; Zainafree, Intan; Aidil Fitrah, Muhammad; Utomo , Dewi Natalista Dwi (Panakeia Journal of Epidemiology, 2024)
Most studies tended to focus on the association of health conditions or tantrum behavior in toddlers with maternal mental health. This study aimed to determine the differences in WHO SRQ-20 scores and the association of WHO SRQ-20 outcomes with fecal disposal factors and drinking water sources. This study used secondary data from RISKESDAS 2018, involving 670 mothers with children aged 6-23 months. The WHO SRQ-20 questionnaire was used to measure general mental health disorders. Mann-Whitney analysis was conducted to determine the difference in scores, while Chi-Square was used to examine the association of WHO SRQ-20 outcomes with toddler feces disposal factors and drinking water sources. All analyses were performed using SPSS 22.0, with a significance value of <0.05. The analysis showed that inappropriate fecal disposal and poor drinking water sources increased the total WHO SRQ-20 score (p=0.003, & p=0.041). Both factors were positively correlated with seven common mental health symptoms in mothers with children aged 6-23 months, including no appetite, difficulty thinking, difficulty making decisions, feelings of fear, trembling hands, and indigestion, with significant p-values (p<0.05) for each symptom. Environmental quality, especially inappropriate fecal disposal and poor drinking water sources, was significantly correlated with increased mental health symptoms among mothers with children aged 6-23 months.